Assessment of the willingness to pay and determinants influencing the large consumers’ perspectives regarding the supply of premium green electricity in South Africa - Moller, Daniel Michiel (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.